The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.15171/jlms.2020.09
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Er:YAG Laser and MI Paste Plus on the Treatment of White Spot Lesions

Abstract: Introduction: White spot lesions (WSLs) occurring after orthodontic treatment lead to patient dissatisfaction and aesthetic problems. The role of calcium-phosphate demineralization systems and the Er:YAG laser in the treatment of these lesions has recently been taken into account. This study aimed to investigate the effect of the Er:YAG laser and MI Paste Plus on the treatment of WSLs. Methods: A total of 65 premolars extracted due to orthodontic treatment were studied in this research. To create enamel lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…Based on penetration depth, our study revealed no significant difference in the CSH values between the different treatments at different depths. These results are congruent with Yassaei 29 , who recorded no statistical significance of artificial saliva group and MI Paste Plus® at different depths. It may be attributed to the wide range of hardness, tooth variability and different mineral content of bovine enamel surfaces.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on penetration depth, our study revealed no significant difference in the CSH values between the different treatments at different depths. These results are congruent with Yassaei 29 , who recorded no statistical significance of artificial saliva group and MI Paste Plus® at different depths. It may be attributed to the wide range of hardness, tooth variability and different mineral content of bovine enamel surfaces.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, CPP-ACP showed no significant difference from the artificial saliva group, which is supported by other studies 29,30 . Mostly CPP-ACP imparts sub-surface remineralization with subsequent resistance to demineralization 31 .…”
Section: Discussionsupporting
confidence: 84%
“…For hardness measurements, a section was made in the center of each block, and one of the halves was embedded in acrylic resin and gradually polished. One sequence of 14 indentations was created at different distances (5,10,15,20,25,30,40,50,70,90,110,130,220, and 330 μm) from the surface of the enamel, in the central region of the blocks, using a Micromet 5114 hardness tester (Buehler ) with a Knoop diamond indenter under a 5 g load for 10 s. Integrated hardness (KHN × μm) for the lesion into sound enamel was calculated by the trapezoidal rule (GraphPad Prism, version 3.02) and subtracted from the integrated hardness for sound enamel to obtain the integrated area of the subsurface regions in the enamel, obtaining the integrated loss of subsurface hardness (∆KHN; KHN × μm). 9,22 Analysis of the profile and depth of subsurface lesions using polarized light microscopy After cross-sectional hardness analysis, the enamel blocks (n = 12/group) embedded in acrilyc resin were sectioned to obtain slices of 300 µm and ground to a thickness of ~100 um using 400 grit paper (Paper Discs,30-5108-320, Buehler) at grinder polisher (Phoenix Beta with Vector Powerhead, Buehler), under constant water refrigeration.…”
Section: Analysis Of Enamel Hardnessmentioning
confidence: 99%
“…The casein phosphopeptide amorphous calcium phosphate (CPP-ACP) complex links to and utilizes casein phosphopeptide (CPP) to stabilize amorphous calcium phosphate (ACP). 10 The addition of CPP to the acquired salivary pellicle decreases S. mutans adherence significantly. Furthermore, the high concentrations of extracellular free calcium dispensed by CPP-ACP complexes may increase the permeability of the streptococcus membrane and promote partial lysis.…”
Section: Introductionmentioning
confidence: 99%
“…Following incubation at 37°C, the colonies in each plate were counted after 96 hr. The primary colony count was recorded for the purpose of comparison with the final count [26].…”
Section: Scanning Electron Microscopic (Sem) Assessmentmentioning
confidence: 99%